2001
DOI: 10.3989/scimar.2001.65s1269
|View full text |Cite
|
Sign up to set email alerts
|

Wind and tide current prediction using a 3D finite difference model in the Ría de Vigo (NW Spain)

Abstract: SUMMARY: A 3D barotropic finite difference model was adapted to reproduce the dynamics of the Ría de Vigo estuary, in the north-west corner of Spain. The model has been applied with astronomical tide and observed wind forcing data. The results are compared to data obtained by an AANDERAA DCM 12 acoustic Doppler current meter at one point of the Ría.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…First, the wind can explain most of the current's variability found in the northern mouth, and even some diurnal peaks are the result of wind forcing, thus showing that current's response to wind forcing is very quick, with a lag of only a few hours between the beginning of the forcing and the resulting currents. Second, the wind currents can overcome tidal currents, as can be seen from experimental data and as was also found with wind‐ and tide‐driven simulations [ Souto et al , 2001]. Third, all the water column at the northern mouth moves basically in the same direction, without the formation of a two‐layer structure.…”
Section: Hamsom Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…First, the wind can explain most of the current's variability found in the northern mouth, and even some diurnal peaks are the result of wind forcing, thus showing that current's response to wind forcing is very quick, with a lag of only a few hours between the beginning of the forcing and the resulting currents. Second, the wind currents can overcome tidal currents, as can be seen from experimental data and as was also found with wind‐ and tide‐driven simulations [ Souto et al , 2001]. Third, all the water column at the northern mouth moves basically in the same direction, without the formation of a two‐layer structure.…”
Section: Hamsom Resultsmentioning
confidence: 56%
“…Thus the river inflow was set to zero (the barotropic river effect is neglected), steadiness and uniformity were assumed for the thermohaline fields and evaporation, precipitation and air sea heat exchange were not allowed. In this way it will be shown that the remote wind is usually the most important forcing agent in the Ría de Vigo [ Rosón et al , 1997; Álvarez‐Salgado et al , 2000; Souto , 2000; Souto et al , 2001], extending its influence even at high (tidal) frequencies. The wind stress forcing at the sea surface was calculated through using data from the meteorological station of the INM at Cape Fisterra.…”
Section: Hamsom Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the dominance of the external wind forcing, the penetration of southwesterlies into the middle ria, as seen here and suggested by Souto et al . [], implies that local wind may also play a significant role in extending the inverse circulation inside the ria through direct drag [ Bowden , ; Csanady , ], wave‐current interactions [ Signell et al ., ] and modulation of the straining of the density field [ Scully et al ., ; Chen and Sanford , ; Li and Li , ]. For instance, Torres López et al .…”
Section: Discussionmentioning
confidence: 99%
“…A new tool has been recently introduced for the study of the remote wind‐induced circulation of the rías: Torres‐López et al [2001] and Souto et al [2001, 2003] applied the GHER (GeoHydrodynamics and Environment Research) and HANSOM (HAmburg Shelf Ocean Model) numerical models, respectively. They compared simulated with experimental data to conclude that the typical estuarine two‐layered circulation pattern of the inner and middle Ría de Vigo overlaps with the alongshore circulation of the ría, which results from the interaction of shelf winds and the intricate topography of the coast.…”
Section: Introductionmentioning
confidence: 99%